Crisis of the Euro Zone as a Core-Periphery Problem - Peťko, Dominik (2014)
The thesis points at roots of the euro zone crisis in its periphery. By comparing the convergence effects on PIIGS and the CEE countries, it shows that some countries should not have adopted euro and preserved national currencies instead. The proposed solution traces parallels to the USA and envisages further fiscal unionisation of the EU.